2016
DOI: 10.1007/s10460-016-9724-1
|View full text |Cite
|
Sign up to set email alerts
|

What difference does income make for Community Supported Agriculture (CSA) members in California? Comparing lower-income and higher-income households

Abstract: In the U.S. there has been considerable interest in connecting low-income households to alternative food networks (AFNs) like Community Supported Agriculture (CSA). To learn more about this possibility we conducted a statewide survey of CSA members in California. A total of 1,149 members from 41 CSAs responded. Here we answer the research question: How do CSA members' (1) socioeconomic and demographic backgrounds, (2) household conditions potentially interfering with membership, and (3) CSA membership experien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

12
65
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 55 publications
(89 citation statements)
references
References 38 publications
12
65
0
1
Order By: Relevance
“…Corresponding with prior research, we found members and farmers to be motivated by a range of personal, social, environmental, and economic objectives [13][14][15][16]20,[25][26][27][28][29][30][31][32][33][34]. As noted by Ostrom [15] (p. 109), for many, the decision to participate in CSA is based on a "complex interplay between self-interest and social values".…”
Section: Discussionsupporting
confidence: 74%
See 4 more Smart Citations
“…Corresponding with prior research, we found members and farmers to be motivated by a range of personal, social, environmental, and economic objectives [13][14][15][16]20,[25][26][27][28][29][30][31][32][33][34]. As noted by Ostrom [15] (p. 109), for many, the decision to participate in CSA is based on a "complex interplay between self-interest and social values".…”
Section: Discussionsupporting
confidence: 74%
“…Promotion: As has been observed in prior research [16,28], members and farmers in our study discussed the power of marketing through social networks. This reinforces the importance of building a community of recurring members that serve as ambassadors for the CSA and engage in indirect promotion by sharing their positive experiences with their networks.…”
Section: Discussionsupporting
confidence: 62%
See 3 more Smart Citations